The Linguistic Landscape of National Shipping Vessels (PELNI) in Indonesia - Risman Iye; Erniati; Dian B.; Fithriyah Inda Nur Abida (Linguistik Indonesia, 2026)
This study investigates the linguistic landscape of the Indonesian National Shipping Company (PELNI) vessels, focusing on signage related to navigation, facilities, safety, and behavioral regulation. Data were collected through systematic documentation of room labels, prohibition signs, facility information, safety instructions, and general notices, and were supplemented by participatory observation and informal interviews with passengers and crew. The analysis reveals that the linguistic landscape is dominated by top-down signage produced by institutional authorities, with Indonesian consistently occupying the primary position, while English appears selectively as a supplementary language. Drawing on Landry and Bourhis’s (1997) framework, the study demonstrates that signage on PELNI ships serves both informational and symbolic functions: guiding spatial navigation and ensuring passenger safety, while simultaneously communicating institutional authority and reinforcing national identity. The results indicate that multilingual signage effectively coordinates safety procedures and administrative compliance, establishing the ship as a site of state authority. Ultimately, this research clarifies how the physical arrangement of signs on the Surabaya-Jayapura route manages passenger movement and enforces institutional rules within a confined maritime setting.